Biological treatment of cattle slaughterhouse wastewater and biogas production using upflow anaerobic sludge blanket reactors - Musa, Mohammed Ali (2020)
Cattle slaughterhouses generate wastewater rich in organic contaminants and nutrients and are considered as high strength wastewater and a potential candidate for treatment processes that recover energy. Komplex Abattoir Shah Alam lack adequate and effective treatment facilities, especially for energy recovery. As a result, a large volume of extremely complex effluent with a high content of chemical oxygen demand (COD) (32,000 mg/L), biological oxygen demand (BOD) (17,158 mg/L), fats, oil and grease (FOG) (1,024 mg/L), color (16,426 Pt-Co) and turbidity (12,500 FAU) is discharged into a water body. However, the department of environment (DOE) Malaysia have set a standard limits A (COD = 120 mg/L) and B (COD = 200 mg/L) to be complied by all intending investors capable of generating waste to be discharge as wastewater. Conventionally, the treatment methods of municipal wastewater are similar to cattle slaughterhouse wastewater treatment. These includes physicochemical and biological treatment methods. Physicochemical methods includes Dissolve air floatation (DAF), coagulation-flocculation and sedimentation, electrocoagulation process and membrane technology. However, the major drawbacks of the physicochemical methods includes, energy intensive, large volume of sludge production, high investment and operation and maintenance cost, and complex infrastructure. Biological treatment methods includes anaerobic, aerobic, facultative lagoons, activated sludge process and trickling filters. Among the biological treatment methods, anaerobic digestion using conventional upflow anaerobic sludge blanket (UASB) reactor appeared to be promising. Nevertheless, its drawbacks range from the long startup period due slow growing microorganism, sludge washout at low hydraulic retention time (HRT), scum formation on the substrate surface and suspended solid accumulation at high inflow velocity. Therefore, in view of the disadvantages raised, the conventional UASB reactor was modified by introducing a synthetic grass as attached growth with large surface area for microbial attachment and a filter within the reactor to reduce sludge washout along with suspended solid to overcome the stated problems. The aim of this work was to determine the biochemical methane potential (BMP) of the cattle slaughterhouse wastewater (CSWW) and study the performance of conventional R1 and a modified R2 UASB reactors treating the CSWW in terms of water quality output at different organic loading rate (OLR). Due to the potential of the CSWW to produce energy, the work further evaluates the performance of the system at varied OLR and constant hydraulic retention time (HRT) with respect to biogas production. Studies have consistently shown that UASB reactors usually requires post treatment of the effluent in order to comply with standard discharge limits and as such, the work further examine the effect of increasing HRT on the best performing reactor in order to determine the optimum HRT to which substantial amount of organic matter will be anaerobically degraded. The BMP test result showed that ratio 1:1 produced the highest biogas with a specific methane production (SMP) of 0.25 LCH4/gCODremoved, while the performance of the laboratory scale conventional (R1) and a modified (R2) UASB reactors treating CSWW under mesophilic condition (35°C) revealed that both reactors achieved COD and BOD removal efficiency (> 90 %) between OLR 1.75, 3, 5 g L⁻¹d⁻¹, and the methane composition was found as 71, 67, and 72 % in R1, while R2 stood 88, 83, and 85 % respectively. The corresponding specific methane production (SMP) in R1 were 0.21, 0.15, 0.12 LCH4/g CODadded, while R2 recorded 0.28, 0.19, and 0.18 LCH4/g CODadded respectively. However, increasing OLR to 10 g L⁻¹d⁻¹ increases the biogas production and COD removal efficiency of R2 at 24 HRT, on the other hand an overall decrease in monitoring parameters of R1, with COD removal, biogas and methane production being 48 %, 8 L/d, and 44 %. Comparatively, the UASB reactor R2 showed high tolerance to increasing OLR and found to be more stable than reactor R1 under the same OLR. This could be due to lower VFA concentrations in R2, especially acetic, propionic and butyric acids than in the reactor R1. Scanning electron microscopy (SEM) analysis showed that R2 was dominated by Methanosarcina bacterial species, while R1 revealed a sludge with insufficient microbial biomass. Moreover, increasing HRT in R2 consistently removed over 90 % COD, with a biogas and methane production reaching 38 L/d and 85 % after 48 h. Coccoidal shaped Methanosarcina microbial population were predominant at the end of performance study of the R2. Furthermore, a steady-state mathematical model developed based on the Monod and modified Stover-Kincannon for bacterial growth, were describe the data obtained from the modified UASB reactor R2. The best fit values was found with the Modified Stover-Kincannon model with a high correlation coefﬁcient (R2 > 0.99). The present study revealed that the UASB reactor R2 has excellent removal efficiency compared to conventional UASB reactor R1, in the treatment of CSWW. A comparison of conventional and a modified upflow anaerobic sludge blanket (UASB) reactors highlighted the advantage of the modified system over conventional and other comparable technologies. The anaerobic modified bioreactor achieves much better performance than would be seen if conventional anaerobic systems were used in the treatment of cattle slaughterhouse wastewaters.